Desafios E Sustentabilidade No Manejo De Plantas 2 2020
DOI: 10.22533/at.ed.7112027054
|View full text |Cite
|
Sign up to set email alerts
|

Produção E Qualidade De Frutos De Amoreira-Preta Submetida a Diferentes Intensidades De Podas

Abstract: Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição 4.0 Internacional (CC BY 4.0). O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding the number of fruits per plant (Table 2), it was observed that the treatment with 8 stems per plant was the most satisfactory, considering that these did not lose in mass. More intense pruning can result in lower productivity, due to the reduction of floral buds (Calai et al, 2020), however, for all treatments, the number of fruits per plant was relatively low when compared to other studies, such as Broetto et al (2009) and Marchi et al (2015). This may have occurred due to atypical conditions during the execution of the work, in which the plants took about 45 days after pruning to start flowering, when, during this period, the days were already hot, so it was necessary to use irrigation, which resulted in plants with high vegetative vigor, and consequent reduction of the productive period.…”
Section: /6mentioning
confidence: 99%
“…Regarding the number of fruits per plant (Table 2), it was observed that the treatment with 8 stems per plant was the most satisfactory, considering that these did not lose in mass. More intense pruning can result in lower productivity, due to the reduction of floral buds (Calai et al, 2020), however, for all treatments, the number of fruits per plant was relatively low when compared to other studies, such as Broetto et al (2009) and Marchi et al (2015). This may have occurred due to atypical conditions during the execution of the work, in which the plants took about 45 days after pruning to start flowering, when, during this period, the days were already hot, so it was necessary to use irrigation, which resulted in plants with high vegetative vigor, and consequent reduction of the productive period.…”
Section: /6mentioning
confidence: 99%